Statistics : Practice makes perfect - McCune, Sandra K. (New York, 2010)
Offers a no-nonsense practical guide to statistics, providing concise summaries, clear model examples, and plenty of practice, making this workbook the ideal complement to class study or self-study, preparation for exams or a brush-up on rusty skills.
Keywords: Mathematical statistics - Problems, exercises